SPECIFICITY AND EFFECTIVENESS OF REPRESENTATION BY LAWYERS OF THIRD PARTIES - George-Bogdan IONIȚĂ (Challenges of the Knowledge Society)
This study seeks to deepen the institution of the representation by lawyer of third parties, combining in this sense the provisions of the current Code of Civil Procedure in the matter of representation as well as the provisions of Law no. 51/1995, the State of the lawyer profession as well as the Code of Ethics regarding the actual activity of the lawyer provided under the legal assistance contract in the case of representing a third party intervening in a legal proceeding. In order to carry out this study, we will analyse the legislation in force, treaties, courses, commentary codes such as monographs published by established authors in the field of civil procedural law, but also decisions pronounced by national and European courts with relevance and impact in the analysis of the institutions addressed.